The Development of Biomimetic Spherical Hydroxyapatite/Polyamide 66 Biocomposites as Bone Repair Materials - Xuesong Zhang; Ming Lu; Yan Wang; Xiaojing Su; Xuelian Zhang (International Journal of Polymer Science)
A novel biomedical material composed of spherical hydroxyapatite (s-HA) and polyamide 66 (PA) biocomposite (s-HA/PA) was prepared, and its composition, mechanical properties, and cytocompatibility were characterized and evaluated. The results showed that HA distributed uniformly in the s-HA/PA matrix. Strong molecule interactions and chemical bonds were presented between the s-HA and PA in the composites confirmed by IR and XRD. The composite had excellent compressive strength in the range between 95 and 132 MPa, close to that of natural bone. In vitro experiments showed the s-HA/PA composite could improve cell growth, proliferation, and differentiation. Therefore, the developed s-HA/PA composites in this study might be used for tissue engineering and bone repair.